Common Ownership, Concentration and Corporate Conduct - Martin C. Schmalz (Center for Economic Studies and ifo Institute (CESifo), 2018)
The question of whether and how partial common-ownership links between strategically interacting firms affect firm behavior has been the subject of theoretical inquiry for decades. Since then, consolidation and increasing concentration in the asset-management industry has led to more pronounced common ownership concentration (CoOCo). Moreover, recent empirical research has provided evidence consistent with the literature's key predictions. The resulting antitrust concerns have received much attention from policy makers worldwide. However, the implications are more general: CoOCo affects the objective function of the firm, and therefore has implications for all subfields of economics studying corporate conduct - including corporate governance, strategy, industrial organization, and all of financial economics. This article connects the papers establishing the theoretical foundations, reviews the empirical and legal literatures, and discusses challenges and opportunities for future research.
Keywords: 330; ownership; control; network; industry concentration; antitrust; objective of the firm; shareholder unanimity